Global vs central obesity and some risk factors among adolescents of a municipality of Venezuela (Revista Venezolana de Salud Pública, 2018)
The objective was to determine the prevalence of global and central obesity in school adolescents of Iribarren Municipality and some risk factors. A cross-association and prevalence study was conducted.  800 adolescents between 15 and 19 years old (405 men) were studied. The two-stage sampling was performed: a) random stratified selecction of 31 institutions according to their educational level; b) accidental non-probabilistic selection of adolescents. Body mass index (BMI) and waist to height ratio (WHR) were measured. Questionnaires on eating habits and physical activity were applied. Socioeconomic status (SES), birth weight of young and parental BMI were obtained with questionnaires administered to parents. The prevalence of global and central obesity were 8.5% and 37.3%, respectively. The independent risk factors for central obesity were being female, 18 or 19 years old and overweight both parents. This risk is increased in women of SES IV and V. The independent risk factors for global obesity were 18 or 19 years old, SES I, II and III and overweight both parents. Male gender and low birth weight were risk factors for global obesity dependent on other factors. It can conclude that the WHR identified more obeses than BMI, so it is important to know the prevalence of global and central obesity, as well as the risk factors, in order to implement effective prevention and control against the severe pandemic of obesity.
Keywords: Obesity; teenagers; Risk factors